Analisis Not in Employment, Education or Training (NEET) pada Usia Muda di Indonesia - Diah Novita Sari; Irdam Ahmad (Jurnal Ketenagakerjaan, 2021)
In the way to face demographic bonus in Indonesia, it is important for the government to maximize the absorption rate of young people in the labor market. For this reason, it is necessary to conduct an analysis of youth in the labor market. Not in Employment, Education or Training (NEET) statistics can accommodate analysis of youth in the labor market. Compared to unemployment statistics, NEET statistics are able to provide a more comprehensive analysis of youth. In Indonesia, the NEET rate tends to be high and stagnant above twenty percent. However, the analysis related to NEET in Indonesia has not been widely carried out. In this study, analysis was carried out with a quantitative approach. The unit of analysis in this study is individuals aged 15-24 years with a coverage area throughout Indonesia. This study uses secondary data in the form of raw data, namely Sakernas August 2017 data. The analytical method used is the binary logistic regression method. In this study, it was found that the interaction variable between sex and marital status, the interaction variable between marital status and age, the parental education variable, and the disability variable affected the NEET status at a young age in Indonesia.